Romania : 2007 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Romania. (IMF Staff Country Reports; Country Report, 2007)
The 2007 Article IV Consultation explains Romania's fiscal and income policies and financial sector issues. The economic outlook is clouded by a widening current account imbalance and the risk of a resurgence of inflation pressures, as a result of strong domestic demand that is being fuelled by rapid credit growth and procyclical fiscal and incomes policies. Executive Directors emphasized the need for policies that reduce vulnerabilities, support sustainable growth, and maximize the gains from EU membership.